CTNNB1-related neurodevelopmental disorder mimics cerebral palsy: case report - Lee, Jaewoong; Yoo, Jaeeun; Lee, Seungok; Jang, Dae-Hyun (Frontiers in Pediatrics, 2023)
While somatic gain-of-function mutations in the CTNNB1 gene cause diverse malignancies, germline loss-of-function mutations cause neurodevelopmental disorders or familial exudative vitreoretinopathy. In particular, CTNNB1-related neurodevelopmental disorders have various phenotypes, and a genotype-phenotype relationship has not been established. We treated two patients with CTNNB1-related neurodevelopmental disorder whose clinical features were similar to those of cerebral palsy, hindering diagnosis.